2012
DOI: 10.1021/cs3002308
|View full text |Cite
|
Sign up to set email alerts
|

Iridium–Ruthenium Alloyed Nanoparticles for the Ethanol Oxidation Fuel Cell Reactions

Abstract: In this study, carbon supported Ir−Ru nanoparticles with average sizes ranging from 2.9 to 3.7 nm were prepared using a polyol method. The combined characterization techniques, that is, scanning transmission electron microscopy equipped with electron energy loss spectroscopy, high resolution transmission electron microscopy, energy dispersive X-ray spectroscopy, and X-ray diffraction, were used to determine an Ir−Ru alloy nanostructure. Both cyclic voltammetry and chronoamperometry (CA) results demonstrate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 40 publications
0
43
0
Order By: Relevance
“…1,2 Most of ethanol SRR catalysts are based on transition-metal (TM) particles supported on oxide compounds, namely, TM particles of Fe, Co, Ni, Cu, Ru, Rh, Pd, Ag, Ir, Pt, and Au supported on oxides such as MgO, La 2 O 3 , ZnO, CeO 2 , Al 2 O 3 , ZrO 2 , V 2 O 5 , SnO 2 , and SiO 2 have been studied for ethanol SRR. [1][2][3][6][7][8][9][10][11][12][13][14] Among those TM/oxides systems, Co/ZnO, 14 Rh/Al 2 O 3 , Rh/CeO 2 , 15 and Ni/La 2 O 3 −Al 2 O 3 , 13 have yielded excellent performance, [1][2][3]8 however, it depends also on the catalysts preparation method, which can affect ethanol conversion and H 2 selectivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Most of ethanol SRR catalysts are based on transition-metal (TM) particles supported on oxide compounds, namely, TM particles of Fe, Co, Ni, Cu, Ru, Rh, Pd, Ag, Ir, Pt, and Au supported on oxides such as MgO, La 2 O 3 , ZnO, CeO 2 , Al 2 O 3 , ZrO 2 , V 2 O 5 , SnO 2 , and SiO 2 have been studied for ethanol SRR. [1][2][3][6][7][8][9][10][11][12][13][14] Among those TM/oxides systems, Co/ZnO, 14 Rh/Al 2 O 3 , Rh/CeO 2 , 15 and Ni/La 2 O 3 −Al 2 O 3 , 13 have yielded excellent performance, [1][2][3]8 however, it depends also on the catalysts preparation method, which can affect ethanol conversion and H 2 selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Although several experimental studies have been reported for ethanol SRR on TM NPs supported on oxides, [1][2][3][6][7][8][9][10][11][12][13][14]23,24 there is a lack of theoretical studies to obtain an atomistic understanding of the interaction of ethanol and water with TM particles with few atoms. For example, most of the experimental 25,26 and theoretical [26][27][28][29][30][31][32][33][34][35] studies have focused on the study of the interaction of water and ethanol with compact TM surfaces employing density functional theory 36,37 (DFT) and the slab geometry model.…”
Section: Introductionmentioning
confidence: 99%
“…Iridium and its oxides has been described as good co-catalyst, and when combined with Pt, PtRu and PtSn it increases the alcohols oxidation in acidic medium. [69][70][71][72] The addition of iridium and its oxides improves the catalytic activity and stability of these materials due to the preferential adsorption of hydroxyl groups on these species at lower potentials, favoring the oxidation of the ethanol intermediates adsorbed in the catalyst surface. inset of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Acetaldehyde was an intermediate product, but the major product of ethanol oxidation on Ir electrodes was acetic acid. The addition of a second element such as Sn [85,86] or Ru [87] remarkably increases the EOR activity of Ir. By CV measurements at room temperature, the peak current value on Ir/C was lower than that on Pt/C, in agreement with Fujiwara et al [83] However, the onset potential of ethanol electro-oxidation on Ir/C was much lower than on Pt/C.…”
Section: Ethanol Oxidation On Pt-free Ir and Ir-m Catalystsmentioning
confidence: 99%